Markers of criticality in phase synchronization - Botcharova, Maria; Farmer, Simon F.; Berthouze, Luc (Frontiers in Systems Neuroscience, 2014)
The concept of the brain as a critical dynamical system is very attractive because systems close to criticality are thought to maximise their dynamic range of information processing and communication. To date, there have been two key experimental observations in support of this hypothesis: i) neuronal avalanches with power law distribution of size and ii) long-range temporal correlations (LRTCs) in the amplitude of neural oscillations. The case for how these maximise dynamic range of information processing and communication is still being made and because a significant substrate for information coding and transmission is neural synchrony it is of interest to link synchronisation measures with those of criticality. We propose a framework for characterising criticality in synchronisation based on a new metric of phase synchronisation (rate of change of phase difference) and a set of methods we have developed centred around the detection of LRTCs. We test this framework against two classical models of criticality (Ising and Kuramoto) and recently described variants of these models aimed to more closely represent human brain dynamics. From these simulations we determine the parameters at which these systems show evidence of LRTCs in phase synchronisation. We demonstrate proof of principle by analysing pairs of human simultaneous EEG and EMG time series, suggesting that LRTCs of corticomuscular phase synchronisation can be detected in the resting state and experimentally manipulated. The existence of LRTCs in fluctuations of phase synchronisation suggests that these fluctuations are governed by non-local behaviour, with all scales contributing to system behaviour. This has important implications regarding the conditions under which one should expect to see LRTCs in phase synchronisation. Specifically, brain resting states may exhibit LRTCs reflecting a state of readiness facilitating rapid task-dependent shifts towards and away from synchronous states that abolish LRTCs.